Recursive algorithm for spectral factorization - Anderson, B.; Hitz, K.; Diem, N. (IEEE transactions on circuits and systems, 1974)
This paper describes a recursive computational algorithm for computing spectral factors of continuous-time and discrete-time power spectrum matrices. The matrices need not be positive definite. Convergence rates of the recursive equation are studied.